Ta có:
\(2x=3y=6z\)
\(\Rightarrow\)\(\frac{2x}{6}=\frac{3y}{6}=\frac{6z}{6}\)
\(\Rightarrow\)\(\frac{x}{3}=\frac{y}{2}=\frac{2z}{2}=\frac{x+y-2z}{3+2-2}=\frac{27}{3}=9\)
\(\Rightarrow\hept{\begin{cases}\frac{x}{3}=9\\\frac{y}{3}=9\\\frac{2z}{2}=9\end{cases}}\)\(\Rightarrow\hept{\begin{cases}x=27\\y=18\\z=9\end{cases}}\)
xin cho tui sửa lại tí @@
Ta có: \(2x=3y=6z\)
\(=>\frac{2x}{6}=\frac{3y}{6}=\frac{6z}{6}\)
\(=>\frac{x}{3}=\frac{y}{2}=\frac{2z}{2}\)
Áp dụng t/c dãy tỉ số bằng nhau, ta có:
\(\frac{x+y-2z}{3+2-2}=\frac{27}{3}=9\)
\(=>\hept{\begin{cases}\frac{x}{3}=9=>x=9\cdot3=27\\\frac{y}{2}=9=>y=9\cdot2=18\\\frac{2z}{2}=9=>z=9\cdot2:2=9\end{cases}}\)
Vậy: x = 27
y = 18
z = 9